Effects of ULF wave power on relativistic radiation belt electrons: 8–9 October 2012 geomagnetic storm. Issue 12 (14th December 2016) - Pokhotelov, D.; Rae, I. J.; Murphy, K. R.; Mann, I. R.
Abstract: Electromagnetic ultralow‐frequency (ULF) waves are known to play a substantial role in radial transport, acceleration, and loss of relativistic particles trapped in the Earth's outer radiation belt. Using in situ observations by multiple spacecraft operating in the vicinity of outer radiation belts, we analyze the temporal and spatial behavior of ULF waves throughout the geomagnetic storm of 8–9 October 2012 and compare with the dynamics of relativistic electron fluxes on board the twin Van Allen Probes spacecraft. The analysis shows that the relativistic electron fluxes reduce from their prestorm levels during the first phase of the storm and rapidly increase during the second phase of the storm. We demonstrate that the behavior of ULF wave power changes throughout the storm, from ULF oscillations being a mixture of compressional and shear magnetic components during the first phase of the storm to ULF oscillations being dominated by transverse (shear) components during the second phase. We analyze the parameters of ULF‐driven radial diffusion throughout the storm and compare the observed diffusion coefficients with their statistical averages. We demonstrate that the observed diffusion coefficients are strong enough to impact the redistribution of relativistic electron fluxes from and to the outer boundary of radiation belts and the diffusion might influence the effects of any local electron acceleration by transporting fluxes inward or outward according to phase space density gradients. Key Points: ULF wave behavior is analyzed throughout 8–9 October 2012 geomagnetic storm using multiple satellite missions Impact of ULF waves on the transport of radiation belt electrons is quantified by computing radial diffusion coefficients The behavior of ULF waves changes throughout the storm from being dominated by compressional waves to being dominated by shear waves